Bridging the Deficiency Divide: Expressions of Non-deficiency Models of Disability in Health Care - Baker, Dana Lee (Disability Studies Quarterly, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>Modern disability theory is based on non-deficiency based models of disability. However, progress in the construction of disability theory outside medicine may have outpaced the uptake of new paradigms of disability by health care professionals. Incomplete rejection of deficiency models of disability is expected by disability scholars and activists to routinely occur in health care scholarship and settings, thereby curtailing the influence of disability studies on the daily lives of individuals both with and without disabilities. Although this anticipated theoretical gap is frequently noted, it has been less often empirically examined. Using data collected from a survey of parents and primary caregivers with autism, this article employs the case of autism to examine the manifestation of non-deficiency based models of disability in health care settings and interactions. The results of the study indicate some uptake of non-deficiency based models of disability.